Pengaruh Variasi Holding Time Pada Proses Heat Treatment (Hardening) Untuk Baja S50c Sebagai Pisau Mesin Pencacah Kayu - Alfariji Munandar, Muhammad Hisson; Kardiman, Kardiman; Santoso, Deri Teguh (Universitas Nusantara PGRI Kediri, 2023)
S50C Alloy Steel is a widely produced and used medium carbon alloy steel, which serves as a raw material for manufacturing machine components, building structures, tools, and one of them being knife blades for wood chippers. The aim of this research is to determine the hardness value and microstructural changes in S50C steel after the heat treatment of hardening and holding time. The method used in this study is an experimental method, where S50C steel is subjected to heat treatment at a temperature of 850°C, followed by different holding times of 30, 60, and 90 minutes, and then cooled using oil. The research results show that the highest hardness value in S50C steel, treated with rapid cooling using oil, has an average hardness value of 589.29 HV after a 90-minute holding time, compared to the raw material's hardness of 262.67 HV. Microstructural testing reveals that the microstructure of the raw material consists of ferrite and pearlite with balanced crystal shape and size, in accordance with a carbon content of 0.50%. In the group of specimens undergoing rapid cooling with oil in the hardening process, a new microstructure called martensite is obtained, which is the main structure responsible for the increased hardness of the steel.